GENDER ISSUES TOWARD GENDER-RESPONSIVE TVTED CURRICULUM PRACTICES - Alinea, Jess Mark L. (Trường Đại học Đà Lạt, 2024)
Gender mainstreaming in technical and vocational education and training (TVET) and the labor market is a goal that is not yet fully achieved. Despite social, political, and economic changes, disparities, discrimination, and bias persist. The lack of gender responsiveness in school-based pedagogy has hindered women’s access, retention, and performance in TVET institutions. While gender imbalances exist in TVET, teachers are often unaware or unwilling to address them, implying that they lack the knowledge to deal with gender issues in practice. Thus, this study was conducted to identify the emerging gender issues that hinder gender responsiveness in technical-vocational teacher education (TVTEd) curriculum practices. The cultural-historical activity theory (CHAT) was used as the theoretical lens to generate and analyze the data. The data were generated from document analysis, interviews, and focus group discussions among teachers, students, and graduates. Having gender-responsive curriculum practice as the object of the study, findings revealed that subjects (teachers) create the main contradictions in emerging gender issues. These are characterized by gender biases, stereotyping that hinders women’s progress in technical-vocational fields, and stereotypes in resources, content, and language. The subject was followed by the contradiction within the rules, tools, community, and division of labor. The study recommends interventions to hone gender responsiveness and thereby mainstream gender in TVTEd curriculum practices. Policy-practice gaps should also be studied and gender-related research in TVET and technical-vocational teacher education should be initiated and funded.